Computing of truss structure using MATLAB - Bakosova, Alzbeta; Krmela, Jan; Handrik, Marian (Manufacturing Technology Journal, 2020)
Trusses are commonly used structure in industrial buildings, warehouses, bridges, transmission tower etc. The analysis of the truss structure design is necessary in order to ensure stable and economical system. This paper presents application for computing planar truss structures that was programmed in environment of MATLAB App Designer using finite element method (FEM). App Designer is programming environment used for creating computing applications with graphical user interface (GUI). The created application for trusses allows users to create geometrical model of the truss structure and input material data, perform static analysis, modal analysis and to optimize truss structure in order to minimize its weight. To ensure accuracy of results, test calculations was performed using commercial software and compared with results from the created application.
Keywords: Truss; MATLAB; Finite element method